STUDENTS’ CRITICAL THINKING REFLECTED IN THEIR WRITTEN RESPONSES ON NICENET - Qudwatin Nisak, M. Isa; Risdaneva Risdaneva; Fitri Anizar (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2018)
This research was conducted to analyze the student’s critical thinking in writing responses on Nicenet Internet Classroom Assistant (ICA) based on Anderson and Krathwohl theory. It is a qualitative research with content analysis method. The subject of this research was the document of students’ responses in online class Nicenet ICA in Communication Management subject that was conducted in semester seven in 2014, batch 2010 and 2011 in the Department of English Language Education of UIN Ar-Raniry Banda Aceh. The result of this study suggested that participating in Nicenet ICA gave positive effects on students in increasing their critical thinking skill in writing. This can be seen through the final result that 92.30% of those documents represent the critical thinking ability in the highest level while the rest were in the medium. It can be inferred from this study that the use of Nicenet as a media of learning can promote and develop the students’ critical thinking skill.